Pelatihan Keterampilan Bermain Musik Pada Anak Sekolah Dasar Melalui Program Ekstrakurikuler - Ridwan Ardi (Jurnal Abdi Masyarakat dan Pemberdayaan Inovatif, 2025)
This community service aims to train elementary school children's music playing skills through a structured and sustainable extracurricular program. Music plays an important role in children's cognitive, social, and emotional development, so this program is designed to improve musical skills while shaping their character and creativity. This activity is carried out with a direct practice approach using simple musical instruments such as angklung, pianica, and guitar, which are easily accessible and played by children. The methods used in this program include routine training, children's song-based learning, and periodic evaluation of skill development. Routine training is carried out once a week with the guidance of experienced educators in the field of music. Children's song-based learning is chosen so that children can more easily understand the concepts of rhythm, melody, and harmony in a fun way. In addition, a group-based approach is applied to build children's cooperation and self-confidence when performing together. The results of the activity showed a significant increase in children's musical abilities, especially in terms of technical skills in playing musical instruments, understanding simple notation, and increasing sensitivity to rhythm and melody. In addition, this program also has a positive impact on increasing children's interest in music, strengthening teamwork, and improving their social and emotional aspects, such as self-confidence and discipline. With the results achieved, this program is expected to become an effective music learning model and be widely applied in other elementary schools